2019
DOI: 10.1108/ijoem-01-2019-0026
|View full text |Cite
|
Sign up to set email alerts
|

Transformational leadership and employee engagement in Trinidad’s service sector

Abstract: Purpose The purpose of this paper is twofold: investigate job resources as a moderator in the relationship between transformational leadership and employee engagement in service sector organizations, and investigate the relative importance of each dimension of job resources in relation to employee engagement. Design/methodology/approach Quantitative data were collected using a survey design for which 187 employees responded. These employees were sourced from retail stores across ten shopping malls located in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
49
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 52 publications
(73 reference statements)
5
49
0
3
Order By: Relevance
“…Align with recent findings of the previous studies, it is suggested that transformational leadership can enhance employee engagement (Balwant, Mohammed, & Singh, 2019). The researchers affirmed that there is a strong positive relationship between transformational leadership and employee engagement.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Align with recent findings of the previous studies, it is suggested that transformational leadership can enhance employee engagement (Balwant, Mohammed, & Singh, 2019). The researchers affirmed that there is a strong positive relationship between transformational leadership and employee engagement.…”
Section: Discussionsupporting
confidence: 80%
“…These 15 items catered to 5 different dimensions including vision, inspirational communication, intellectual stimulation, supportive leadership, and personal recognition. A past study by Balwant, Mohammed, and Singh (2019) had used this instrument with attained Cronbach alpha value result of 0.92. Employee voice was tested adapting the 6-item scale from Botero and Van Dyne (2009).…”
Section: Measurementmentioning
confidence: 99%
“…Work engagement (WE) in the last couple of decades has been greatly considered as a mediating variable that links various HRM-related antecedents and positive job-related outcomes (Balwant et al, 2019). WE was described by Schaufelli et al (2002) as "a positive attitude towards work indicated by vigor, dedication, and absorption".…”
mentioning
confidence: 99%
“…Job resources have no effect on employee engagement mediated by workplace spirituality, meaning that the relationship is not directly mediated workplace spirituality will only further weaken the relationship job resources toward employee engagement, it indicates that a same kin the opportunity to develop as an indicator of the most dominant of job resources given will not improve employee engagement and when added to the sense of openness among employees as the most dominant indicator of workplace spirituality cannot change the relationship of job resources to employee engagement, this statement is supported by [40] and [19] who stated that job resources had no effect on employee engagement and were not supported by research conducted by [42] and [41] stated that job resources had a positive and significant effect [12], [13] and [18] stated that spirituality in the workplace has a significant effect on employee engagement.…”
Section: Discussionmentioning
confidence: 83%
“…Job resources have no effect on employee engagement, this means that no matter how good job resources are, they will not give high employee engagement results and vice versa, this result is supported by the results of research by [40] and [19] which provides research results that job resources have no effect on employee engagement but this research is not supported by research by [42] and [41] which state that job resources have a significant positive effect on employee engagement. Judging from the most dominant indicators on the job resources variable, namely promotion and employee engagement, namely enthusiasm, this can be interpreted that existing job promotions cannot significantly increase employee engagement in the company.…”
Section: Discussionmentioning
confidence: 91%